(Be) like en anglais, genre en français : de la prosodie comme commentaire subjectif - Jeanne VIGNERON-BOSBACH (E-REA)
This study aims at contrasting (be) like and genre as triggers of direct speech. Like appears mostly in the well-studied be like structure which has now become a true contender of say when reporting direct speech. Genre, on the other hand, appears in more diverse constructions, although the locution faire genre seems to be productive but not limited to direct quotation. In a contrastive approach, we will first describe how be like and genre function as quotatives of direct speech by observing them in examples from spoken corpora. We will then attempt to show how they can represent two opposite ways of expressing subjectivity (neutral - polemic). Finally, we will focus on the way those two quotatives mark out the frontier between the quoting and the quoted segments, and how they interact with prosody to materialize this frontier. Furthermore, we will see that this acoustic feature may represent a form of subjective comment on the quoted speech.